Appendicitis in Children in a Large Italian COVID-19 Pandemic Area - La Pergola, Enrico; Sgrò, Alberto; Rebosio, Federico; Vavassori, Daniele; Fava, Giorgio; Codrich, Daniela; Montanaro, Beatrice; Leva, Ernesto; Schleef, Jurgen; Cheli, M.; Pelizzo, Gloria; Gamba, Piergiorgio; et al. (Frontiers in Pediatrics, 2020)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic has dramatically changed the routine activities of pediatric surgical centers, and it determined the reduction of admissions in the pediatric emergency departments (PED). We reviewed the records of patients affected by acute appendicitis (AA) during the COVID-19 pandemic period in a large Italian COVID-19 pandemic area. Methods: Data regarding demographics, age, macroscopic and microscopic findings, and time between symptom onset and PED admission of patients affected by confirmed AA in the period between March and April 2020 were considered. The data were compared with those obtained during the same period of 2019, 2018, and 2017 in the included centers. Data were quoted as median (range) or absolute number. Non-parametric statistical tests were used to compare groups. A p ≤ 0.05 was regarded as significant. Since only anonymous data have been used and the data storage meets current data protection regulations, ethical committee approval was not required for this study. Results: Eighty-six patients underwent surgical appendectomy for AA between February 20th, 2020 and April 20th, 2020; 32.5% were complicated appendicitis and 67.5% were uncomplicated. Fifty-three patients were males and 33 were females. Patients' age ranged from 3 to 17 years and the median age was 10 years. The median time between the onset of symptoms and the admission in PED was 1.85 days. The average time between the symptom onset and PED admission was 1.8 days. Conclusions: Although fear from the COVID-19 pandemic determined a delayed diagnosis of serious pediatric diseases, the increasing prevalence and severity of AA were not demonstrated in the most COVID-19-affected areas of Italy.